Digital Student Agenda For Junior School During Home-Based Learning - Wiputra Cendana; Yonathan Winardi; Robert H. Soesanto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
The purposes of this research are to investigate the needs and expectations from primary teachers of having a digital student agenda and develop a suggested model to be used during home-based learning. Open-ended questionnaire was distributed to primary teachers in a private Christian school located in Tangerang and an interview was done with the head of academic coordinator as well as with the primary curriculum coordinator to collect data. At the same time, a digital student agenda model was constructed, considering its possibilities to cover affective and spiritual aspects that allow more holistic development in the primary students lives assisted by their parents. A research and development research method was used to produce a suggested model of a digital student agenda. The results show that both primary teachers and the academic coordinator agree to have a digital student agenda that promotes more communication between teachers and parents. It is recommended this preliminary research is followed by a micro and macro-scale testing to ensure its reliability and further expanded use.